The Relationship Between Breastfeeding Techniques and Physical Problems in Breastfeeding Mothers (Mastitis, Sore Nipples, and Breast Milk Retention) - Susilawati Jainahu; Rani Safitri (Institut Nalanda, 2025)
The breastfeeding period is a crucial period in supporting infant growth and development, where proper breastfeeding techniques are essential to prevent various physical problems in mothers such as mastitis, sore nipples, and breast milk engorgement. This study aims to analyze the relationship between breastfeeding techniques and the incidence of physical problems in breastfeeding mothers. The study design used a cross-sectional analytical approach involving 30 breastfeeding mothers aged 0–6 months at the Kobe Community Health Center. Data were collected through questionnaires regarding breastfeeding techniques and physical complaints, then analyzed using the Chi-Square test. The results showed that sore nipples were the most common complaint (33.3 %), followed by breast milk engorgement (23.3%) and mastitis (16.7%). Bivariate tests showed a significant relationship between breastfeeding techniques and mastitis (p=0.05) , sore nipples (p=0.02), and breast milk engorgement (p=0.04), where mothers who used inappropriate breastfeeding techniques were at higher risk of experiencing physical complaints. This study concludes that breastfeeding techniques play an important role in preventing physical problems in breastfeeding mothers, so breastfeeding education and support from health workers are very necessary to increase the success of exclusive breastfeeding.